A new species of corkscrew plant (Genlisea, Lentibulariaceae) from the Amazon lowlands of Brazil, including a key to all species occurring north of the Amazon River - Fleischmann, Andreas; Costa, Suzana M.; Bittrich, Volker; Do Carmo Estanislau Do Amaral, Maria; Hopkins, Michael (Phytotaxa, 2017)
A new species of Genlisea section Genlisea from the white-sand savannas (“campinaranas”) of Brazilian Amazon is described and illustrated, providing remarks on habitat and ecology as well as SEM seed images. Genlisea multiflora has been recorded from Viruá National Park, and is of affinity to the large, purple-flowered species G. sanariapoana and G. guianensis. An identification key to all Genlisea species north of the Amazon is presented.